COMPARISON OF THE THERMOCATALYTIC REFORMING OF SEWAGE SLUDGE TO ITS PYROLYSIS - Onyishi, Hillary; Fox, Ariana; Pech, Jael; Neidel, Johannes; Daschner, Robert; Apfelbacher, Andreas; Hornung, Andreas (European Biomass Conference and Exhibition Proceedings, 2024)
This work investigates the fundamental differences between pyrolysis and thermocatalytic reforming (TCR®). The TCR®, developed by the Fraunhofer UMSICHT, is an extension of pyrolysis in that it involves intermediate pyrolysis in an auger reactor and catalytic reforming in a post-reformer. A TCR® plant can be converted back to a pyrolysis plant when the post-reforming phase is deactivated. In this work, sewage sludge is tried in both the TCR® and the pyrolysis arrangements using a lab-scale TCR® plant. The pyrolysis experiments are carried out at temperatures of 450 and 600 °C while the TCR® experiments are carried out a reactor temperature of 450 °C each and post-reformer temperatures of 600 and 750 °C. The results show that intermediate pyrolysis produces greater biooil and process water yields and the TCR® generally produces greater amounts of biochar while their biogas yields seem the same. But it is observed that the hydrogen fraction of the gas from pyrolysis is minimal while that of the gas from the TCR® is up to 40 vol.%. In either case, the hydrogen fraction increases with increasing prevailing temperature and, in the case of pyrolysis, with increasing solid residence time. The results agree with predictions from literature. Therefore, the TCR® can be said to be the more suited technology for the valorisation of biomass.
CRIS-Team Scopus Importer:2024-12-06
Keywords: biofuels; biomass; hydrogen.; pyrolysis; thermocatalytic reforming